2013
DOI: 10.1530/edm-13-0048
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of hyperandrogenism in pregnancy: clinical features and differential diagnosis

Abstract: SummaryBackgroundHyperandrogenic states in pregnancy are rare but arise most commonly due to new-onset ovarian pathology in pregnancy. We describe the case of a young woman who presented in the latter half of her pregnancy with features of hyperandrogenism. We review the biochemical and imaging findings and discuss the differential diagnosis.Case presentationA 26-year-old woman presented in the later part of her pregnancy with widespread hirsutism. Biochemical testing confirmed hyperandrogenism (testosterone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is a benign, ethnically related condition that does not need any medical intervention. Other conditions, such as diffuse neonatal hypertrichosis in newborns, may be related to maternal hyperandrogenism, which in turn may be linked to polycystic ovarian syndrome and potentially associated with type 1 maternal diabetes, although ear pinnae hypertrichosis has not been described in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…This is a benign, ethnically related condition that does not need any medical intervention. Other conditions, such as diffuse neonatal hypertrichosis in newborns, may be related to maternal hyperandrogenism, which in turn may be linked to polycystic ovarian syndrome and potentially associated with type 1 maternal diabetes, although ear pinnae hypertrichosis has not been described in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The 2003 Rotterdam consensus workshop concluded that PCOS was a syndrome with two out of three criteria: (i) oligoor anovulation; (ii) clinical and/or biochemical signs of hyperandrogenism; and (iii) polycystic ovaries (PCO) of ultrasound imaging (with the exclusion of other aetiologies) (Rotterdam, 2004). Hyperandrogenism often presents abnormal biochemical parameters (elevated serum concentrations of testosterone, free testosterone, androstenedione, dehydroepiandrosterone sulphate) (Gluszak et al, 2012), and/or clinical signs (acne, hirsutism, seborrhea, androgenic alopecia, virilization) (Das et al, 2013). The mechanism of hyperandrogenism is still unclear, although the ovarian origin of androgen is well studied (Schweighofer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%